Breastfeeding and child development - Emla Fitzsimons; Marcos Vera-Hernández (Institute for Fiscal Studies (IFS), 2021)
We show that children who are born at or just before the weekend are less likely to be breastfed, owing to poorer breastfeeding support services in hospitals at weekends. We use this variation to estimate the effect of breastfeeding on children's development in the first five years of life, for a sample of births of low educated mothers. We find large effects of breastfeeding on children's cognitive development but no effects on health or non-cognitive development during the period of childhood we consider. Regarding mechanisms, we study how breastfeeding affects parental investments and the quality of the mother-child relationship.
Keywords: I14; I18; J13; 330; Kinder; Ernährung; Kognition; Gesundheit; Sozialer Indikator; Theorie